2012
DOI: 10.1590/s1678-91992012000400003
|View full text |Cite
|
Sign up to set email alerts
|

Dangerous scorpion fauna of Mali

Abstract: Abstract:Although the main Malian scorpion species of medical interest, Androctonus amoreuxi, is responsible for severe envenomings and perhaps some deaths, it has hitherto been considered not dangerous for humans. This population is located in the Saharian North-Eastern regions of Mali where it is accompanied by Leiurus quinquestriatus, a well known dangerous species of the Sahara. In the Gao district, divided by the Niger River, less desolate than the Tessalit and Kidal regions, one specimen of the dangerous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Most scorpion stings occurred in Mali, where scorpionism was also described among the civilian population. 11,12 According to these studies, most scorpion stings occurred at night, during the summer months, and at home.…”
Section: Discussionmentioning
confidence: 99%
“…Most scorpion stings occurred in Mali, where scorpionism was also described among the civilian population. 11,12 According to these studies, most scorpion stings occurred at night, during the summer months, and at home.…”
Section: Discussionmentioning
confidence: 99%
“…Four of the scorpion species found in Sudan have highly potent venom and are thus regarded as medically significant: Androctonus amoreuxi, A. australis, Leiurus quinquestriatus and Parabuthus abyssinicus. For accounts of these species' toxicity, also in neighbouring countries, see Cilli and Corazzi (1946), Adi-Bessalem et al (2008), Goyffon et al (2012), Soliman et al (2013) and Ali and Ali (2015). The two Androctonus species, colloquially known as 'fat-tailed scorpions', were previously known only in Sudan from Northern State in the north of the country (Dunlop et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In a generalist study, Goyffon & Billiald [26] suggested the presence of L. quinquestriatus in Mauritania; however, in absence of any evidence. In a similar study Goyffon et al [27] associated L. quinquestriatus to a population in Mali. This identification proceeded by non-experts is most certainly erroneous and this Malian population probably has more connections with L. hoggarensis or even with an undescribed form.…”
Section: One Particular Example: the Genus Leiurus In Africamentioning
confidence: 94%